2021
DOI: 10.3390/cells10051073
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells as Therapeutic Targets in Uterine Cervical and Endometrial Cancers

Abstract: Uterine cervical and endometrial cancers are the two most common gynecological malignancies. As demonstrated in other types of solid malignancies, an increased number of circulating or tumor-infiltrating myeloid-derived suppressor cells (MDSCs) have also been observed in uterine cervical and endometrial cancers, and increased MDSCs are associated with an advanced stage, a short survival, or a poor response to chemotherapy or radiotherapy. In murine models of uterine cervical and endometrial cancers, MDSCs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…One study [ 164 ] conveyed that elevated MDSCs in gastrointestinal cancers could serve as an independent prognostic factor for decreased survival, normally linked with an elevation of IL-13, arginase-1, and Tregs. Similar findings are also described in gynecological cancers [ 165 , 166 ]. Shimura et al [ 167 ] indicated that immune suppression mediated by G-CSF-induced MDSCs could be the reason leading to the poor prognosis in gynecological cancer patients.…”
Section: Mdscs In Patients With Solid Tumorssupporting
confidence: 88%
“…One study [ 164 ] conveyed that elevated MDSCs in gastrointestinal cancers could serve as an independent prognostic factor for decreased survival, normally linked with an elevation of IL-13, arginase-1, and Tregs. Similar findings are also described in gynecological cancers [ 165 , 166 ]. Shimura et al [ 167 ] indicated that immune suppression mediated by G-CSF-induced MDSCs could be the reason leading to the poor prognosis in gynecological cancer patients.…”
Section: Mdscs In Patients With Solid Tumorssupporting
confidence: 88%
“…MDSCs are immature myeloid cells with immune suppressive action based on L-arginine depletion in the tumor microenvironment, causing T-cell receptor downregulation [36]. MDSC levels are higher in EC than in normal endometrium [30], increase with advanced stage disease, and are associated with poor prognosis and poor response to cytotoxic treatments [37]. Tumor-associated macrophages (TAMs) are also involved in EC immune escape.…”
Section: Other Immune-response Related Features In Endometrial Cancermentioning
confidence: 99%
“…Similar to “premetastatic niche” models of distant sites, according to which the primary tumor “prepares” a potential metastatic site to “better accommodate” future metastatic cells, the premetastatic lymph node niche (PLNN) model has also been suggested. The interest in characterizing a possible premetastatic lymph node niche lies in characterizing the metastatic potential of a certain tumor, since a premetastatic niche favoring the dissemination of tumor cells would constitute the first key step in the metastatic cascade, and, thus, identify the best potential molecular targets [ 4 , 5 , 6 ]. The PLNN is characterized, according to preclinical models, by the development of an immunosuppressive immune microenvironment, especially driven by myeloid-derived suppressor cells (MDSCs), which are currently promising therapeutic targets [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in characterizing a possible premetastatic lymph node niche lies in characterizing the metastatic potential of a certain tumor, since a premetastatic niche favoring the dissemination of tumor cells would constitute the first key step in the metastatic cascade, and, thus, identify the best potential molecular targets [ 4 , 5 , 6 ]. The PLNN is characterized, according to preclinical models, by the development of an immunosuppressive immune microenvironment, especially driven by myeloid-derived suppressor cells (MDSCs), which are currently promising therapeutic targets [ 4 , 5 , 6 ]. MDSCs are produced after stimulation by molecules or vesicles (exosomes) secreted by tumor cells, and they act as T-cell suppressors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation